About how „the soul of the nation tunes in on the model of its native surroundings" - Sylwia Nowak-Bajcar, (Balcanica Posnaniensia. Acta et studia, 2023)
When a project for the comprehensive modernization of the Serbian capital Belgrade was conceived in the late 1860s, an altruistic concern for the health of society was a constant element of most discussions devoted to this problem. When the modernization process of the Serbian capital Belgrade was continued in the late 1860s, an altruistic concern for the health of the society was a constant element of most statements devoted to this problem. The health discourse, apart from the aesthetic one, was an element connecting the reflection on the city in Western Europe and Serbia. However, while in the West attempts to heal urban space were supposed to be an antidote to the negative effects of industrialization, in relation to Belgrade these treatments resulted from completely different premises, namely, they were motivated by the legacy of the times of industrial backwardness as a result of Turkish rule. Urban green areas played a special role in the process of modernizing Belgrade. The concern for them in the statements of Serbian architects and town planners of the interwar period, presented as a touchstone of modernity, was in fact included in the mission of strengthening dynastic interests, based on „national forest myth-making”. In the article I present the mechanisms of designing a historical and political filter on nature, which are one of the strategies of including it in the processes of creating and strengthening the ideology of „integral Yugoslavism”, hidden under the slogans of modernizing the capital of the Kingdom of Yugoslavia by greening it.